2015
DOI: 10.1111/tct.12421
|View full text |Cite
|
Sign up to set email alerts
|

E-learning and near-peer teaching in electrocardiogram education: a randomised trial

Abstract: Both teaching styles were well received by students and improved their confidence in ECG interpretation. Near-peer teaching led to superior scores in our final assessment. Given the congested nature of the modern medical curriculum, direct comparison of the efficacy of these methods may aid course design. The aim of this study is to compare the efficacy of e-learning and near-peer teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 8 publications
1
52
0
Order By: Relevance
“…6 Alternatively, in vestigators studying the best method to teach second year medical students in their introductory class on electrocardiographic material randomized "nearpeer" teaching (physicians in their second postgraduate year using a 1hour PowerPoint presentation) and elearning (including short multiplechoice assessments). 482 Al though both groups increased knowledge, the near peer group scored significantly higher (84%) than the e learning group (74.5%). A facetoface component may be important for students without prior knowledge of ECG, whereas elearning may be appropriate for build *The content of electrocardiographic monitoring education needs to match the nature and complexity of the patient population served.…”
Section: Education Of Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Alternatively, in vestigators studying the best method to teach second year medical students in their introductory class on electrocardiographic material randomized "nearpeer" teaching (physicians in their second postgraduate year using a 1hour PowerPoint presentation) and elearning (including short multiplechoice assessments). 482 Al though both groups increased knowledge, the near peer group scored significantly higher (84%) than the e learning group (74.5%). A facetoface component may be important for students without prior knowledge of ECG, whereas elearning may be appropriate for build *The content of electrocardiographic monitoring education needs to match the nature and complexity of the patient population served.…”
Section: Education Of Staffmentioning
confidence: 99%
“…Knowledge can be enhanced by collaborative activities such as preceptorships, skill validations, and case studies, 16,[481][482][483][484][485][486] and studies have demonstrated no differences in knowledge or confidence with faceto face classes versus a hybrid approach (ie, online course combined with facetoface classes). 482,487,488 Hospital, service line, or unitbased nurse educa tors or clinical nurse specialists can provide this edu cation. 485,487,488 In addition, the manufacturer of the monitors used should provide education related to the equipment.…”
Section: Education Of Staffmentioning
confidence: 99%
“…Deficiencies in the interpretation of ECG abnormalities, including critical life-threatening abnormalities, have been identified in several studies of undergraduate [11] and postgraduate learners [12][13][14]. ECG interpretation is taught in medical school through a variety of methods [15][16][17], but there is no agreement on the most effective approach [18].…”
Section: Introductionmentioning
confidence: 99%
“…The value of NPT is becoming increasingly recognised in medical education and provides benefit both to the near-peer tutor and the learner. [3][4][5] NPT nurtures the concept of continued professional development (CPD) and provides the opportunity for the tutor to develop their teaching skills. For the learner, it can create a non-threatening learning environment, with information carefully targeted to their educational needs.…”
Section: Introductionmentioning
confidence: 99%